Review of portable near infrared spectrometers: Current status and new techniques. Issue 2 (April 2022) - Zhu, Chenxi; Fu, Xiaping; Zhang, Jianyi; Qin, Kai; Wu, Chuanyu
Near infrared (NIR) spectroscopy is a non-destructive detection technology involving NIR spectral data acquisition and chemometric treatment. The use of an NIR spectrometer is evidently crucial in this regard; however, traditional benchtop NIR spectrometers considerably limit usage scenarios. Accordingly, the miniaturization of spectrometers with high level performance has become a research trend. Various commercial products have been developed, and new techniques have been applied to produce more portable NIR spectrometers. This paper reviews the main types of commercial portable NIR spectrometers and summarizes as well as compares their specifications. Moreover, new techniques for promoting miniaturization and the prospects for future development are introduced.